Perbedaan Daya Tahan Jantung Paru Mahasiswa (Literature Review) - Alfarizi, Lalu Mariawan; Anam, Khaerul; Syahroni, Mohammad (Universitas Hamzanwadi, 2022)
Physical condition is one of the important factors that must be possessed by every player in an effort to achieve maximum performance. Good physical condition ability is characterized by players having good cardio-pulmonary endurance. Cardiopulmonary endurance is the highest value at which a person can consume oxygen during exercise. Cardio-pulmonary endurance can be increased by physical exercises such as fartlek and continuous running. The purpose of this study was to determine the differences in cardio-pulmonary endurance in futsal UKM and soccer UKM in the Nahdlatul Ulama University, NTB. This research is a quantitative study with an experimental design with a randomized pretest posttest two group design. The number of research samples was 26 people who were divided into two groups. Group 1 consisted of 13 people from UKM futsal and group 2 consisted of 13 people from UKM UKM. This research was conducted at the Krisna Mataram futsal field. Cardiopulmonary endurance was measured by the multi fitness test (MFT) the difference was tested by independent sample t-test. The results of this study indicate that there is no significant difference between the cardiopulmonary endurance of the two groups. The results of this research can later be used as a reference in making an exercise program. Whether it's short term, medium term, and long term training programs. Pulmonary endurance is very important in supporting one's achievements. Therefore it is hoped that students in futsal UKM and soccer UKM have good cardiovascular endurance.